Human-Like Endtip Stiffness Modulation Inspires Dexterous Manipulation With Robotic Hands - Anna Shafer; Ashish D. Deshpande (IEEE, 2022)
We present a novel method for biomechanically inspired mechanical and control design by quantifying stable manipulation regions in 3D space for tendon-driven systems. Using this method, we present an analysis of the stiffness properties for a human-like index finger and thumb. Although some studies have previously evaluated biomechanical stiffness for grasping and manipulation, no prior works have evaluated the effect of anatomical stiffness parameters throughout the reachable workspace of the index finger or thumb. The passive stiffness model of biomechanically accurate tendon-driven human-like fingers enables analysis of conservatively passive stable regions. The passive stiffness model of the index finger shows that the greatest stiffness ellipsoid volume is aligned to efficiently oppose the anatomical thumb. The thumb model reveals that the greatest stiffness aligns with abduction/adduction near the index finger and shifts to align with the flexion axes for more efficient opposition of the ring or little fingers. Based on these models, biomechanically inspired stiffness controllers that efficiently utilize the underlying stiffness properties while maximizing task criteria can be developed. Trajectory tracking tasks are experimentally tested on the index finger to show the effect of stiffness and stability boundaries on performance.